2016
DOI: 10.3389/fncom.2016.00007
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal Muscle Synergy Activation Patterns Generalize their Motor Function across Postures

Abstract: We used a musculoskeletal model to investigate the possible biomechanical and neural bases of using consistent muscle synergy patterns to produce functional motor outputs across different biomechanical conditions, which we define as generalizability. Experimental studies in cats demonstrate that the same muscle synergies are used during reactive postural responses at widely varying configurations, producing similarly-oriented endpoint force vectors with respect to the limb axis. However, whether generalizabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 104 publications
1
13
0
Order By: Relevance
“…These results are further supported by findings from a novel simulation of the local spinal circuits showing proprioception from muscles contribute to synergy level organization of motor control in humans during isometric tasks. Whilst our results are largely in line with previously established literature regarding synergy recruitment, we differ in our finding that joint angle and therefore afferent feedback regarding joint position alters synergy recruitment (Torres-Oviedo, Macpherson, and Ting 2006;Roh, Rymer, and Beer 2012;Sohn and Ting 2016). We propose that in this case, because the available synergies are constrained due to the nature of an isometric task, adaptation is achieved through changes in recruitment.…”
Section: Discussionsupporting
confidence: 72%
“…These results are further supported by findings from a novel simulation of the local spinal circuits showing proprioception from muscles contribute to synergy level organization of motor control in humans during isometric tasks. Whilst our results are largely in line with previously established literature regarding synergy recruitment, we differ in our finding that joint angle and therefore afferent feedback regarding joint position alters synergy recruitment (Torres-Oviedo, Macpherson, and Ting 2006;Roh, Rymer, and Beer 2012;Sohn and Ting 2016). We propose that in this case, because the available synergies are constrained due to the nature of an isometric task, adaptation is achieved through changes in recruitment.…”
Section: Discussionsupporting
confidence: 72%
“…Further, we took advantage of the finding that maximal effort solutions in arm postural control increases limb stability [39] by comprehensively exploring the continuum of solutions along the null-path between the minimum and maximum effort solutions. While we did not explicitly study effects of limb configuration [56][57][58], our prior work showed that non-minimum efforts solutions are more likely to generalize their function across different postures, potentially making them more robust for control [59]. Such robust properties of motor solutions could explain our prior observations that individual differences in motor module, a.k.a., muscle synergy, patterns are observed across limb postures and for different tasks [1,2,9,60,61].…”
Section: Discussionmentioning
confidence: 97%
“…For example, the "bumpiness" of the landscape may explain why habitual versus optimal patterns are preferred [43][44][45]. Although we used two functional properties of effort and stability, other multi-objective criteria can be used such as minimizing trajectory error, energetics [102], and ability to generalize [59,94,103] or switch [104] across motor tasks. Moreover, the multitude of solutions and local minima may support the observation of individual-specific patterns of muscle co-activation that are regularly observed during gait and balance tasks in healthy humans and animals [1,2,9,60,61,105].…”
Section: Discussionmentioning
confidence: 99%
“…Sohn and colleagues [44] present evidence that generalizability does not arise directly from musculoskeletal or optimality constraints. We complement this study by showing directly that synergies are generalizable for upper extremity reaching tasks.…”
Section: Discussionmentioning
confidence: 98%
“…Further, this generalizability of synergies computed from EMG might result from biomechanical constraints, although Sohn and colleagues [44] show that for a postural task in the cat hindlimb, generalizability must be explicitly accounted for in an objective function when computing muscle activations that are accurate across tasks. In simulation studies, researchers have shown that synergies computed for one walking task facilitate the generation of walking dynamics at different speeds [32] and different body weights [31], although both optimizations relied partially on tracking experimental kinematics or kinetics.…”
Section: Introductionmentioning
confidence: 99%